Case Report: Pre-emptive intra-aortic balloon counterpulsation in patients with aortic regurgitation initiated after cross-clamping during cardiopulmonary bypass - Hirschl, David; Muras, Lennart; Schemke, Simon; Vondran, Maximilian; Heringlake, Matthias (Frontiers in Anesthesiology, 2023)
Preoperative implantation of an Intra-aortic balloon pump has been shown to reduce mortality in high-risk cardiac surgery cases. However, one main contraindication for its use is severe aortic regurgitation. We describe a case of the safe and beneficial use in a patient presenting with moderate to severe aortic regurgitation and highly reduced ejection fraction undergoing aortic valve replacement.